What is Religious Misconduct: A Typological Analysis of the Crimes Motivated by Polytheistic Religion, Using the Chinese Folk Religion as an Example - Huang, Hua-Lun (International Journal of Criminology and Sociology, 2019)
In terms of political function, religion is usually defined by criminologists/sociologists as an institution of social control. While religion can assist state managers to maintain the status quo and to safeguard social order, religion, under certain circumstances, can become an antisocial force as well. In this paper, the criminogenic side of religions will be examined. By using the Chinese folk religion as an example, this paper will demonstrate that polytheistic religions can become unstable social organizations. Four topics will be addressed in this paper. First, the research paradigms that can help crime researchers examine the subject of religious misconduct will be summarized. Then the features shared by polytheistic religions will be proposed. The third part will look at the primary traits of Chinese folk religion. Finally, by using the Chinese folk religion as an instance, the diverse contexts under which polytheistic religions can breed deviant/criminal behaviors will be analyzed.